The influence of trust, information technology and communication skill on knowledge transfer in MADA (Muda Agricultural Development Authority) - Sharifah Nur Alia, Syed Mansor (2017)
This study was conducted to investigate the influence of trust, information technology and communication skill on knowledge transfer among extension officer in Muda Agricultural Development Authority (MADA). The aim of this study is to identify the relationship of trust, information technology and communication skill towards knowledge transfer. The dependent variable used in this study is knowledge transfer, whereas the independent variables comprises of trust, information technology and communication skill. This study was done through quantitative approach in which questionnaires were used as a medium to collect data. The respondents for this study were MADA extension officer and 113 questionnaires were distributed. The results of the study showed positive significant relationship between information technology and knowledge transfer.